Islamic Banking in Malaysia: Arbitration Resolution of Financial Disputes and Obstacles to its Spread - Elena V. Sitkareva (Модернизация, инновация, развитие)
Purpose: the article examines the main problems associated with the extension of arbitration of domestic and international Islamic financial disputes in Malaysia. These include the specific features of the legal regulation of Malaysia, excluding the resolution of certain categories of cases by way of arbitration, and the lack of legal certainty in the submission of cross-border contracts in the field of Islamic banking to Sharia law.To achieve this goal in the article you must accomplish the following tasks: to determine whether there are institutions in Malaysia providing arbitration services for disputes in the field of Islamic banking; investigate the reasons for the unwillingness of the parties to a financial dispute to transfer it to arbitration; to identify the main problems of transferring a cross-border financial dispute to international arbitration; to study the practice of international arbitration on this issue.Methods: this article is based on an interdisciplinary concept of research, which allowed to distinguish the distinctive features of the legal regulation of the settlement of financial disputes in Malaysia.Results: currently the popularization of arbitration permits for domestic and international financial disputes in Malaysia faces difficulties due to both internal reasons and the traditional approach of Islamic banks to include in contracts the reservation of subordination of the provisions of the contract to the law of England or the United States in conjunction with the reservation clause financial disputes in the courts and arbitration of these states. Nevertheless, one can assume with great confidence that, following the development of Islamic banking, so-called Islamic arbitration will spread in Malaysia.Conclusions and Relevance: the materials outlined in the article show the special role of arbitration in resolving domestic and international disputes in the field of Islamic banking. Practical application of its results will improve the Russian legislation in the sphere of resolving financial disputes.